2019
DOI: 10.1136/bmjgh-2018-001151
|View full text |Cite
|
Sign up to set email alerts
|

Supportive supervision to improve service delivery in low-income countries: is there a conceptual problem or a strategy problem?

Abstract: Supportive supervision is perceived as an intervention that strengthens the health system, enables health workers to offer quality services and improve performance. Unfortunately, numerous studies show that supervisory mechanisms in many low-income countries (LICs) are suboptimal. Further, the understanding of the concept and its implementation is still shrouded in misinterpretations and inconsistencies. This analysis contributes to a deeper understanding of the concept of supportive supervision and how reorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 32 publications
(51 reference statements)
3
82
0
Order By: Relevance
“…It is therefore not surprising that inspectors compensate for this shortage of funds by soliciting illicit money in the form of bribes. These results agree with similar studies dealing with regulation of the private sector which found that regulation by actors may be hindered by organizational challenges which may not be limited to lack of motivation as a result of inadequate incentives [3,48]. There is a need to identify recurrent funding, especially in low-income countries if inspection especially of retail drug shops is to be sustainable.…”
Section: Discussionsupporting
confidence: 88%
“…It is therefore not surprising that inspectors compensate for this shortage of funds by soliciting illicit money in the form of bribes. These results agree with similar studies dealing with regulation of the private sector which found that regulation by actors may be hindered by organizational challenges which may not be limited to lack of motivation as a result of inadequate incentives [3,48]. There is a need to identify recurrent funding, especially in low-income countries if inspection especially of retail drug shops is to be sustainable.…”
Section: Discussionsupporting
confidence: 88%
“…Originally, the examination comprises several "stations" in which examinees are expected to perform several clinical tasks within a specified period against specific predetermined criteria essential to demonstrate adequate competence for that particular clinical skill. Moreover, the OSCE evaluates areas that are pertinent to the optimal performance of healthcare providers, such as their ability to record/interpret data, problemsolving, teaching, communication, and handling unpredictable patient behavior, which is otherwise impossible in the traditional clinical examination [15].…”
Section: Study Toolmentioning
confidence: 99%
“…However, Bernard's discrimination model does not elaborate in detail the supervision relationship which makes it hard to compare with results of this study. There is growing support for the need to improve supervisor-supervisee relationships because this improves internal support supervision quality rather than supervision frequency which is emphasized by many government agencies involved in supervision at unit level like drug shops in low income countries [32,33]. As far as rural drug sellers are concerned, this can best be achieved when the supervision relationship between the supervisor and drug seller is cordial.…”
Section: Role Modelmentioning
confidence: 99%